Inovasi Pembelajaran Hadis Integratif Sebagai Upaya Merespon Tantangan Dunia Pendidikan Islam - Afwadzi, Benny; Supriyatno, Triyo; Maimun, Agus (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2023)
Islamic education (PAI) faces challenges from various aspects. In many cases, disproportionate interpretations of hadith, one of the PAI’s subject, often cause many problems in society. According to the fact, authors suggest innovations in integrative hadith learning with social sciences to respond to challenges in the world of Islamic education. The authors found several findings using a qualitative approach and a literature study model. First, various Islamic educational challenges are rooted in globalization with the advent of the Industrial Revolution 4.0 and Society 5.0 era. One of the PAI challenges and problems is an atomistic study. Second, various educational innovations were created by the scholars, such as the use of modern information and communication technology (ICT), and the theory of Multiple Intelligence (MI). Third, integrative hadith learning needs to be carried out in the PAI learning, which is interpreted as a material object and social sciences as a formal object. Educators can comprehensively explain the material for discussing hadith comprehensively and have the vision of rahmatan li al-‘alamin. In addition, students will also be able to understand and eliminate the irregularities of the hadith meaning. The authors conclude that integrative hadith learning is very important in PAI learning to respond to the challenges of Islamic education.